(untitled) (Indian Journal of Arid Horticulture, 2025)
Fenugreek is an annual herb, self pollinated, small seeded legume, which is grown as vegetable, fodder and seed crop. Its seeds contain protein, fatty oil, vitamins and minerals. Its seed has been found beneficial in many diseases. Disrupted free radical metabolism in diabetic may be normalized by fenugreek seed supplementation in the diet. So, the diabetic patients should be encouraged to include these medicinal plants in their daily diet to control blood sugar level (Kocchar et al. 2006). Fenugreek is a multipurpose crop whose every part is consumed in one or other form. Productivity of fenugreek can be further enhanced by judicious package of fertilizers especially phosphorus, molybdenum and increasing the availability of phosphorus by seed inoculation with phosphate solubilizing bacteria.